RESOLUTION IN THE 3D MODELING OF OBJECTS FOR ADDITIVE MANUFACTURING AND REVERSE ENGINEERING – SHUTTER EFFECT - COUTIÑO-MORENO, Elvis; ESTRADA, Quirino; MALDONADO-ONOFRE, Daniel; RODRIGUEZ-MENDEZ, Alejandro; GOMEZ-GIRON, Julio (Applied Computer Science, 2021)
This article presents a proportional relationship between Shutter and the value of the resolution scanning system that allows decision making for modeling 3D parts used in reverse engineering and additive manufacturing. As a first step, the object of interest is treated to dim excessive brightness, then the object is scanned (by point cloud or mesh) with the use of a Handyscan 700 scanner. The point cloud is processed with the Geomagic software Desing X to generate a CAD image and a “.stl” file for 3D printing.